Exploring the Scope of Caravan Tourism in Karnataka - Kumar , G. Saravana; Soni , Nagadesi Geetha (Recent Advances in Commerce, Management, and Tourism, 2023)
Caravan tourism is already popular in many foreign countries like USA movements European countries and in the recent years it has spread across many countries and people especially families prefer to travel in their own vehicle for privacy and comfort of movement and choose any good location on the way to stay over -night. Now this concept is becoming popular in India also and this study aims to study the present status and scope of caravan tourism in Karnataka. It has been existing since olden ages when people travelled long distances and camped on the way. Now this concept has become a tourism activity. The main objective of this study is to find the Caravan tourism potential in Karnataka state and to create awareness about Caravan tourism in India. It’s based on primary research with data collected through structured interview with reputed tour operators, Tourism department officials in Karnataka, besides by questionnaire is also data is collected from tourists. This article covers all aspects of caravan tourism, its terminologies and latest government guidelines issued for caravan tourism promotion. The social implication of this study is people will come to know about caravan tourism and there is such option also and about facilities available in the state for such travel and also for entrepreneurs’ opportunities available in promoting caravan parks supported by Government. The results are presented at the end of this article based on valid inputs received from various sources directly. Since there acute shortage of literature from India on Caravan tourism, this article will certainly initiate more research on this topic.